Curriculum Management of Tahsin Al-Qur’an with the Tahajji Method - Anati Rahila; Faridi Faridi; Nurhakim Nurhakim (Yayasan Letiges Konsultan Sosial, 2025)
Management of the Al-Qur'an tahsin curriculum using the tahajji method effectively develops comprehensive Al-Qur'an tahsin learning. It can be implemented for all ages, accompanied by how to spell it through the rules of tajwid (makhorij and shifat letters). This research aims to analyse and describe the Planning, Organising, Implementation, and Evaluation Management of the Tahsin Al-Qur'an curriculum using the Tahajji method at SDTA Kuttab Rumah Qur'an Malang. This research method uses a qualitative descriptive approach with a case study type. Data collection techniques included non-participant observation, semi-structured interviews, and document analysis. The primary sources in this study were the school principal, the vice principal of the Qur'an curriculum, and Qur'an teachers. The data were analysed using Miles and Huberman's interactive model consisting of data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation of sources and methods. The results of this research show that the Tahsin Al-Qur'an Curriculum Management using the Tahajji method at SDTA Kuttab Rumah Qur'an Malang contains several elements, namely: Planning of the Tahsin Al-Qur'an curriculum at SDTA Kuttab Rumah Qur'an is carried out in stages, personally with using the Tahajji/Nurul Bayan method. Organisation of teaching staff at SDTA Kuttab Rumah Qur'an emphasises coordination, division of tasks according to expertise, and quality teacher training. Implementation of learning at SDTA Kuttab Rumah Qur'an is practical and personal, involving school practice, home muroja'ah, and regular weekly evaluations. Evaluation of the SDTA Kuttab Rumah Qur'an curriculum is carried out periodically through observation, feedback from teachers, students, and parents, and continuous improvement.